Promoting unity and cooperation: reviving Ukhuwwah Islamiyyah as a civilisational force and poverty eradication - Murdipi, Rafiqa (Sejahtera Consumerism Kulliyyah of Economics and Management Sciences IIUM, 2025)
The revival of Ukhuwwah Islamiyyah is both a religious aspiration and a fundamental necessity for modern Muslim society. By accepting this holy bond, Muslims can rise above their differences, come together to form a powerful civilisation, and not only work to end poverty but also be a symbol of unity, justice, and compassion for all people. Muslim countries may work together and share knowledge, money, and technology to boost Ukhuwwah and move civilisation forward by making the Ummah more socially cohesive. They may also revitalise Islamic social finance instruments like Zakat, Sadaqah, and Waqf to eradicate poverty and bolster social welfare initiatives.